DESIGN AND MANUFACTURE OF A WASTE COMPACTOR PROTOTYPE: A STEP TOWARDS IMPLEMENTING A NON-BURN HEALTH CARE WASTE DISPOSAL IN DEVELOPING COUNTRIES - Mwinuka, Tito E.; Nyichomba, Bavo B. (Tanzania Journal of Engineering and Technology, 2018)
Non-burn technology is the only safe way of handling and disposing infectious healthcare waste. It involves steam treatment of infectious waste at temperatures higher than 121 o C for a minimum of 30 minutes before disposing them just like other municipal waste. Infectious healthcare waste is normally only about 10 -25% of all healthcare waste. In this paper, design, manufacturing and testing of a waste compactor for reducing waste volume to facilitate its handling is discussed. Preliminary tests show that the waste volume can be reduced to less than 10% of its original volume using the developed compactor. Waste compactors can serve urban hospitals where dumping space is a problem and the waste has to be transported. The compactor, developed by the University of Dar es Salaam team under the UNDP support, is capable of handling up to 25 kg of medical waste at a time and it is hydraulically operated. Furthermore, except for the hydraulic units and other electrical gadgets which can be bought as off-shelf parts, the designed waste compactor can be manufactured locally. The estimated total production cost was below USD 3,000. Part of UNDP requirements for this support was that the compactor design should be adopted by seven countries namely; Argentina, India, Latvia, Lebanon, Philippines, Senegal, Tanzania and Vietnam. These countries were nominated by UNDP to demonstrate the best techniques and practices of non-burn technologies in the developing countries. Keywords: healthcare waste disposal, non-incineration waste disposal, waste compaction.